Microwave-Assisted Hydrolysis of Robusta Coffee Parchment as a Reducing Sugar Feedstock - Khairur Rahman Ilyas; M. Iqbal Samudra; Mizanurafi’ Ghifarhadi Prasiefa (University of Jember, 2024)
The hydrolysis process is a process of breaking down substances by reacting using water, the aim is to break down the substance. This research focuses on the hydrolysis process to determine the reducing sugar content of coffee parchment. The method used is microwave-assisted hydrolysis. This method can increase lignin release more effectively than conventional methods in the process of cellulose and hemicellulose hydrolysis. The most commonly used hydrolysis to hydrolyze cellulose is acid hydrolysis. This research uses coffee parchment raw material (horn skin) which contains cellulose and hemicellulose with HCl solvent. Hydrolysis with acid concentration is (1, 2, and 3%), microwave power (150, 300, and 450 W), and time (20, 25, and 30 minutes). In this study, the optimal reducing sugar yield was 8,054 g/mL under the operating conditions of 25 minutes, 3% HCl concentration, and 450 W microwave power.